Changes in Fungal Community Composition in Response to Elevated Atmospheric CO2 and Nitrogen Fertilization Varies with Soil Horizon - Weber, Carolyn F.; Vilgalys, Rytas; Kuske, Cheryl R. (Frontiers in Microbiology, 2013)
Increasing levels of atmospheric carbon dioxide (CO2) and rates of nitrogen (N)-deposition to forest ecosystems are predicted to alter the structure and function of soil fungal communities, but the spatially heterogeneous distribution of soil fungi has hampered investigations aimed at understanding such impacts. We hypothesized that soil physical and chemical properties and fungal community composition would be differentially impacted by elevated atmospheric CO2 (eCO2) and N-fertilization in spatially separated field samples, in the forest floor, 0-2 cm, 2-5 cm and 5-10 cm depth intervals in a loblolly pine Free-Air-Carbon Dioxide Enrichment (FACE) experiment. In all soils, quantitative PCR-based estimates of fungal biomass were highest in the forest floor. Fungal richness, based on pyrosequencing of the fungal ribosomal large subunit gene, increased in response to N-fertilization in 0-2 cm and forest floor intervals. Composition shifted in forest floor, 0-2 cm and 2-5 cm intervals in response to N-fertilization, but the shift was most distinct in the 0-2 cm interval, in which the largest number of statistically significant changes in soil chemical parameters (i.e phosphorus, organic matter, calcium, pH) was also observed. In the 0-2 cm interval, increased recovery of sequences from the Thelephoraceae, Tricholomataceae, Hypocreaceae, Clavicipitaceae, and Herpotrichiellaceae families and decreased recovery of sequences from the Amanitaceae correlated with N-fertilization. In this same depth interval, Amanitaceae, Tricholomataceae and Herpotriciellaceae sequences were recovered less frequently from soils exposed to eCO2 relative to ambient conditions. These results demonstrated that vertical stratification should be taken into consideration in future efforts to elucidate environmental impacts on fungal communities and their feedbacks on ecosystem processes.